Craniofacial Osteosarcoma—Pilot Study on the Expression of Osteobiologic Characteristics and Hypothesis on Metastasis - Weber, Manuel; Söder, Stephan; Sander, Janina; Ries, Jutta; Geppert, Carol-Immanuel; Kesting, Marco Rainer; Wehrhan, Falk (Frontiers in Oncology, 2020)
Background: Craniofacial osteosarcomas (COS) and extracranial osteosarcomas (EOS) show distinct clinical differences. COS show a remarkably lower incidence of metastases and a better survival. However, in contrast to EOS, they show a poor response to neoadjuvant chemotherapy. Tumor-associated macrophages and their polarization as well as developmental biological signaling pathways are possible candidates for explaining the clinical differences between COS and EOS. The aim of the study was to analyze differential expression of macrophage markers and important regulators of these pathways. Methods: Twenty osteosarcoma cases (10 COS and 10 EOS) were immunohistochemically stained to assess CD68, CD11c, CD163, MRC1, Gli1, and Gli2 expression. Statistical differences between COS and EOS were tested using the Mann–Whitney U test. Additionally, the paper describes an example of multidisciplinary treatment of a patient suffering from COS and discusses the surgical challenges in treatment and rehabilitation of COS. Results: COS showed a significantly (p < 0.05) increased infiltration of CD11c-positive M1 macrophages and a shift toward M1 polarization compared to EOS. Additionally, COS revealed a significantly (p < 0.05) lower Gli1 expression than EOS. Conclusion: The reduced Gli1 expression in COS can be interpreted as reduced activation of the Hedgehog (Hh) signaling pathway. The increased M1 polarization and reduced Hh activation in COS could explain the low incidence of metastases in these osteosarcomas.
CRIS-Team Scopus Importer:2020-07-17
Keywords: craniofacial osteosarcoma; Gli1; hedgehog; M1; M2; macrophage polarization; osteosarcoma of the jaw

The special developmental biology of craniofacial tissues enables the understanding of oral and maxillofacial physiology and diseases - Weber, Manuel; Wehrhan, Falk; Deschner, James; Sander, Janina; Ries, Jutta; Möst, Tobias; Bozec, Aline; Gölz, Lina; Kesting, Marco Rainer; Lutz, Rainer (International Journal of Molecular Sciences, 2021)
Maxillofacial hard tissues have several differences compared to bones of other localiza-tions of the human body. These could be due to the different embryological development of the jaw bones compared to the extracranial skeleton. In particular, the immigration of neuroectodermally differentiated cells of the cranial neural crest (CNC) plays an important role. These cells differ from the mesenchymal structures of the extracranial skeleton. In the ontogenesis of the jaw bones, the development via the intermediate stage of the pharyngeal arches is another special developmental feature. The aim of this review was to illustrate how the development of maxillofacial hard tissues occurs via the cranial neural crest and pharyngeal arches, and what significance this could have for relevant pathologies in maxillofacial surgery, dentistry and orthodontic therapy. The pathogenesis of various growth anomalies and certain syndromes will also be discussed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cranial neural crest; Developmental biology; Maxillofacial development; Orthodontics